2002
DOI: 10.1016/s0370-2693(02)01625-8
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic dipole properties and the triaxial deformation

Abstract: Nuclear magnetic dipole properties of ground bands and gamma-vibrational bands are studied for the first time using the triaxial projected shell model approach. The study is carried out for the Dy and Er isotopic chains, ranging from transitional to well-deformed region. It is found that the g-factor ratio of the 2^+ state in ground bands to that of gamma-bands, r=g(2^+, gamma-vib)/g(2^+, ground), varies along an isotopic chain. With the gamma-deformations, which best reproduce the energy levels for both bands… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the present work, we also evaluate the intraand inter-band electromagnetic transition probabilities, and it is shown that the deformation used in the present work provides a better agreement for the transition calculations in comparison to our earlier work on the ground-state configuration only [26]. The TPSM approach has already been discussed in our earlier publications [12][13][14][15][16][17], and in the following we shall provide only a few details of the model that are relevant to the discussion of the results.…”
mentioning
confidence: 67%
“…In the present work, we also evaluate the intraand inter-band electromagnetic transition probabilities, and it is shown that the deformation used in the present work provides a better agreement for the transition calculations in comparison to our earlier work on the ground-state configuration only [26]. The TPSM approach has already been discussed in our earlier publications [12][13][14][15][16][17], and in the following we shall provide only a few details of the model that are relevant to the discussion of the results.…”
mentioning
confidence: 67%
“…[7]). There have been microscopic models employed in the g factor calculation for heavy, deformed nuclei [8,9,10,11,12,13,14,15]. However, except in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the particle-rotor model analysis of 128 Cs, it is noted that the calculated B(E2) transition probabilities depict the opposite trend to that of the observed transitions as a function of spin [7]. In the present work, we shall provide a detailed investigation of 108 Ag using the microscopic triaxial projected shell model (TPSM) approach [30][31][32]. Recently, TPSM approach has been extended to include multi-quasiparticle states and this development allowed [17,18].…”
mentioning
confidence: 99%